2015
DOI: 10.1007/s13277-015-3354-x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with CCNH/CDK7 facilitates CtBP2 promoting esophageal squamous cell carcinoma (ESCC) metastasis via upregulating epithelial-mesenchymal transition (EMT) progression

Abstract: CtBP2, as a transcriptional corepressor of epithelial-specific genes, has been reported to promote tumor due to upregulating epithelial-mesenchymal transition (EMT) in cancer cells. CtBP2 was also demonstrated to contribute to the proliferation of esophageal squamous cell carcinoma (ESCC) cells through a negative transcriptional regulation of p16(INK4A). In this study, for the first time, we reported that CtBP2 expression, along with CCNH/CDK7, was higher in ESCC tissues with lymph node metastases than in thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…CDK7 was significantly (p < 0.05) negatively correlated with the expression of mesenchymal markers including FN1, VIM and MMP2. Role of CDK7 on cancer metastasis has been reported by one group that CCNH/CDK7 can interact with CtBP2 to promote cell migration of breast cancer [29] and esophageal squamous cell carcinoma [30]. In agreement with our findings, recent studies suggested that CDKs controlled the migration and metastatic potential of cancer cells [31].…”
Section: Discussionsupporting
confidence: 93%
“…CDK7 was significantly (p < 0.05) negatively correlated with the expression of mesenchymal markers including FN1, VIM and MMP2. Role of CDK7 on cancer metastasis has been reported by one group that CCNH/CDK7 can interact with CtBP2 to promote cell migration of breast cancer [29] and esophageal squamous cell carcinoma [30]. In agreement with our findings, recent studies suggested that CDKs controlled the migration and metastatic potential of cancer cells [31].…”
Section: Discussionsupporting
confidence: 93%
“…A549 cells were seeded in 6-well plates (Corning, Inc.) and transfected with NLK-shRNA, control-shRNA and full-length NLK according to the manufacturer's instructions (19). When they reached ~80% confluency 48 h post-transfection, cells were serum-starved for 12 h, then scratched using the fine end of a 100-µl pipette tip.…”
Section: Methodsmentioning
confidence: 99%
“…expression of CtBP2 was upregulated in ESCC tissues (27,28). In addition, CtBP2 predicts a poor prognosis in human cancers, including ESCC (27).…”
Section: C-terminal Binding Protein-2 Mediates Cisplatin Chemoresistamentioning
confidence: 95%